Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Guru SMAN 6 Tasikmalaya - Agit Triyana; Mila Karmila; Barin Barlian (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to examine the influence of leadership style and motivation on the performance of teachers at SMAN 6 in Tasikmalaya City. This study focuses on understanding how several aspects of leadership, such as creating a conducive work environment, implementing discipline, and recognizing teacher contributions, impact their performance and motivation. Data was collected by a structured questionnaire distributed to 49 teachers, encompassing 18 indicators for leadership style, 8 indicators for work motivation, and 10 indicators for performance measured using a Likert scale. This research design is quantitative in nature, aiming to gather empirical evidence on the variables under investigation. Structured questionnaires are utilized to gather data from a sample of teachers at SMAN 6 Tasikmalaya. The research sample consisted of 49 respondents, and data analysis was conducted using SPSS. The research findings indicate that the leadership style of the school principal has a significant positive impact on teacher performance. Key aspects such as maintaining physical facilities, ensuring a clean and comfortable environment, and facilitating effective communication contribute to higher levels of teacher satisfaction and performance. Furthermore, the work motivation of teachers, driven by recognition of their efforts and consistent implementation of discipline, also significantly affects their performance. This finding indicates that both leadership style and work motivation are crucial in enhancing teachers' performance. Effective leadership that supports a positive and disciplined work environment, coupled with enough recognition and appreciation for teachers' contributions, leads to improved teacher performance. This research emphasizes the significance of strategic leadership and motivation in the educational environment, and suggests that school administrators prioritize these factors to achieve better educational outcomes.